Formulation and Evaluation of Gastro-Retentive Floating Tablets of Verapamil Hydrochloride - Shraddha P. Malpani; Dr. Nishan N. Bobade; Dr. Shrikant D. Pande (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Verapamil Hydrochloride has a short biological half-life and undergoes extensive first-pass metabolism, necessitating frequent dosing. Gastro-retentive floating drug delivery systems offer prolonged gastric residence and sustained drug release, thereby improving therapeutic efficacy and patient compliance. Objective: The present study aimed to formulate and evaluate gastro-retentive floating matrix tablets of Verapamil Hydrochloride using HPMC K4M and Xanthan Gum. Methods: Tablets were prepared by the direct compression method using a 3² full factorial design. The formulations were evaluated for drug–polymer compatibility, pre-compression and post-compression characteristics, buoyancy, swelling index, in vitro drug release, drug release kinetics, and stability. Results: FTIR and DSC studies confirmed drug–polymer compatibility. All formulations exhibited satisfactory physical properties and remained buoyant for 12 h. Floating lag time ranged from 62 ± 0.595 to 128 ± 0.598 s, while cumulative drug release after 12 h ranged from 85.1 ± 0.42% to 94.0 ± 0.23%. Drug release followed the Korsmeyer–Peppas model for most formulations, whereas a few exhibited Zero-order kinetics. Formulation F3 showed the shortest floating lag time (62 ± 0.595 s), highest drug release (94.0 ± 0.23%), and satisfactory stability under different storage conditions. Conclusion: The optimized formulation (F3) demonstrated excellent buoyancy, sustained drug release, and stability, indicating its potential as a gastro-retentive floating drug delivery system for Verapamil Hydrochloride.